A Decade of Annual Arctic DOC Export With Polar Surface Water in the East Greenland Current. Issue 20 (23rd October 2020) - Gonçalves‐Araujo, Rafael; Stedmon, Colin A.; de Steur, Laura; Osburn, Christopher L.; Granskog, Mats A.
Abstract: The export of dissolved organic carbon (DOC) from the Arctic Ocean is expected to change due to warming and increased river runoff. Here we present a method to quantify DOC transport with the East Greenland Current combining synoptic and year‐round data (2009–2018). An algorithm based on quantitative and qualitative aspects of colored dissolved organic matter (CDOM) was developed to provide DOC estimates. Combined with mooring‐derived monthly Polar Surface Water (PSW) volume transports, we estimate DOC exports for the period from 2003–2017. For much of the period DOC exports have been reasonably constant at 46.8 (±6.2) Tg yr −1, while the reduction in PSW export in recent years has resulted in lower annual DOC exports (below 39 Tg C yr −1 ). We now have a technique to resolve seasonal and annual fluctuations in Arctic carbon export, offering a significant improvement over earlier bulk estimates and represents a baseline to detect future change. Plain Language Summary: The Arctic Ocean has higher concentrations of dissolved organic carbon (DOC) compared to the other oceans due to the supply from large Siberian rivers that drain expansive carbon‐rich watersheds. Climate change in the Arctic is altering the supply of river water and DOC to the Arctic Ocean. This is eventually expected to also be reflected in the subsequent export of DOC from the Arctic to the North Atlantic via a major gateway, the Fram Strait. Here we present a new approach to quantify the transport of DOC through the Fram Strait based on year‐round mooring data and spectroscopic measurements of colored dissolved organic matter (CDOM). We calculate DOC transports using our measurements over a 10‐yr period, and the results provide a baseline from which to observe future changes in the Arctic Ocean that were not resolved with earlier estimates based on bulk concentrations and bulk volume transports. Key Points: Spectral characteristics of CDOM can predict DOC concentrations in the Fram Strait DOC transports are strongly correlated with Polar Surface Water volume transports from the Arctic Ocean with the East Greenland Current Annual DOC transport estimates for 2009 to 2018 varied between 27 and 60 Tg C yr −1